Efeitos da perda de habitat sobre a comunidade de aves de uma floresta estacional seca do Brasil - Melo, Vaniclézia de Andrade (2013)
Birds are considered sensitive to human disturbance because they have a close relationship with the environmental conditions. In the caatinga, modification of habitat ocurred by a historical process of environmental deterioration as a result of unsustainable use of natural resources. Due to the extreme climatic conditions of the caatinga, it is expected that a more resilient biota survives in this vegetation under to human interventions than those in more stable environments, such as tropical rainforests. Thus, the present study aimed to investigate the effects of habitat loss on a bird community of caatinga area type seasonal dry forest in the municipality of Candiba, Bahia, Brazil, comparing avifaunas occurring in an area of remnant forest (Area I) with adjacent matrix cleared of area (Area II). Six expeditions were conducted, three in the dry season and three in the rainy season, between November 2011 and July 2012. The method of Mackinnon lists was used for recording auditory and visual species. It was recorded 138 species, 92 in the Area I and 94 in the Area II. Both areas showed a low similarity (38%) between their specific compositions, demonstrating that only a small portion of the bird community in the region occurs in both habitat types, tolerating the different states of preservation. Regarding the trophic structure, insectivorous species predominated in both areas, with emphasis on the occurrence species of more specialized habits in only Area I, indicating that they are intolerant to habitat loss. In Area II, were representative species of bird generalist habits, such as granivorous and omnivorous, they seem to benefit from the replacement of native forests by agricultural lands. Although bird species of high sensitivity and forest dependents represented the minority, such species were directly affected by habitat change, since many of them were not recorded in the cleared matrix. Thus, habitat loss is a process that leads to negative effects on the bird community of seasonal dry forest, especially in species composition, which changes as the forest vegetation is removed.